REPRESENTASI CITRA LAKI-LAKI DALAM IKLAN GATSBY STYLING POMADE KAJIAN SEMIOTIKA ROLAND BARTHES - Rahayu, Nur Umi; Afrianto, Damar Tri (Capture : Jurnal Seni Media Rekam, 2017)
Advertising is now creating a need for consumers. Advertising makes the wishes and expectations of consumers as a need that must be met and how the fulfillment of course by consuming the advertised product. This study aims to determine the representation of male image contained in the ad Gatsby Styling Pomade. The type of research used is qualitative research with semiology communication approach. The focus of this study is the representation of the male image formed from the symbols contained in the ad Gatsby Styling Pomade. Analysis technique used in this research is semiotics analysis method with Roland Barthes semiotics analysis approach which has two marking level denotation and connotation and myth. In this ad shows that men should always look perfect with a proportionate body shape and a neat hair. The male image is displayed, forming the notion that men should always look stylish and cool. Then it can be concluded that the image of men found in the ad Gatsby Styling Pomade included in the category of masculine image.Â Kerwords : Advertising, representation, image, semiotics, masculineÂ Â